Двойственные оценки для оптимизационной задачи квадратичного типа на многообразии Штиффеля - Шор, Н.З.; Стецюк, П.И.; Березовский, О.А. (Теорія оптимальних рішень, 2004)
We study the global optimization problem connected to finding of a minimum of homogeneous quadratic function of a special kind on Stiefel manifold. It's considered Lagrange dual bounds for three variants of this problem which differ with restrictions on components orthonormal vectors. It's shown on tests that they can effectively be used for finding of a global minimum.